MAKNA SIMBOLIK GONDANG SABANGUNAN DALAM UPACARA KEMATIAN SAURMATUA PADA MASYARAKAT BATAK TOBA DI PEKANBARU - Sihombing, Martgaretta Elisabet; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Gondang Sabangunan, which consists of: Taganing, Gordang, Sarune, Ogung Oloan, Ogung Ihutan, Ogung Panggora, and Hesek, tools that serve as an announcement to the public that there are parents who died saurmatua. Saurmatua is the death of the person who died had populate both boys and girls. Suhut would make the perfect custom event at the event in accordance with Dalihan saurmatua Na Tolu, such a thing is not necessarily carried out at the sarimatua because of his descendants still not perfect in terms of kinship. For this study aims to know the meaning of symbols of the social object Gondang Sabangunan funerals Saurmatua the Toba Batak people in Pekanbaru, the meaning of symbols of the physical object Gondang Sabangunan funerals Saurmatua the Toba Batak people in Pekanbaru, and the values of what is contained in Saurmatua funeral ceremony in Toba Batak people in Pekanbaru.Research using qualitative research method that produces descriptive data in the form of words written or spoken of the people and behaviors that can be observed. This study uses a theoretical approach of Symbolic Interaction. Informants in this study consisted of traditional leaders, Sabangunan Gondang music players and the community that follows the funeral ceremony saurmatua.The results showed that the symbolic meaning Gondang Sabangunan funerals saurmatua in Batak Toba community in Pekanbaru there are three premises: first the meaning of symbols on social objects in the house that ceremony (upacara dijabu) and the house or yard ceremony (upacara maralaman), the second is meaning of symbols on the object is physical instruments contained in Gondang Sabangunan consists of Taganing, Gordang, Sarune, Ogung Panggora, Ogung Oloan, Ogung Ihutan, Hesek. These three values contained in funerals saurmatua namely social values, religious values, family values.Keywords : Gondang Sabangunan, The meaning of symbols, Ceremony Saurmatua